Certainty Factor Pada Sistem Pakar Diagnosis Penyakit Anak - Rohman, Abdul; Azizah, Ansatul (Universitas Islam Syekh Yusuf, 2023)
The fear of parents when their child experiences health problems with various symptoms but the parents do not understand the type of disease their child is suffering from. However, the schedule of experts or doctors is limited and you have to stand in line. Pediatric consultation services are needed with a doctor or expert who can provide an initial diagnosis of health problems experienced by children from a distance, anywhere and anytime so that parents can find out the type of child's illness. The method applied in the expert system is the Certainty Factor which can provide a certainty value from each knowledge base. The system design method uses a waterfall. This research uses quantitative methods.Based on the functional suitability testing that has been carried out on the expert system for diagnosing children's diseases, the percentage value is 100%. The results of the usability test on the expert pediatric disease diagnosis system, which totaled 40 samples of parents, obtained an average percentage of 87.68%.